Design and Build a Cassava Peeling Machine to Increase Productivity - Gahar Putra Samitra; Cristhoper Setiawan; Joel Siman (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2023)
Cassava (Manihotesculenta) is an agricultural commodity widely used to meet various human needs and increase production. Cassava peeling requires technological improvements, including the peeling process. The L-shaped iron, which is shaped at a right angle, functions as a blade that will rotate and slice the material's surface continuously along with the rotation of the peeling cylinder. This research stage includes functional, structural, and testing approaches. The test parameters on the machine prototype are material mass, percentage of damage due to stripping, rate of unpeeled skin, and stripping efficiency. The smallest weight value and the one with the most significant weight value have a large difference in power value, namely 5.83 Watts. This occurs due to the large voltage and electric current deals, which initially peeling cassava with a diameter of 48 mm were only 4.49 volts and 3.3 amperes, which increased when peeling cassava weighing 52 mm. The current value required was 4.8 volts and 4.3 amperes.